Green process of biomass waste derived fluorescent carbon quantum dots for biological imaging in vitro and in vivo - Ren, Haitao; Yuan, Yue; Labidi, Abdelkader; Dong, Qibing; Zhang, Ke; Lichtfouse, Eric; Allam, Ahmed A.; Ajarem, Jamaan S.; Wang, Chuanyi (Chinese chemical letters, 2023)
In the context of the circular economy, the huge amounts of biomass waste should be converted into value-added materials and energy to diminish pollution, atmospheric CO2 levels and costly waste disposal. Biological imaging usually uses expensive and toxic chemicals e.g., organic dyes, semiconductor quantum dots, calling for safer, greener, cheaper fluorescent probes for biological imaging in vitro and in vivo. In these regards, carbon quantum dots (CQDs)-based fluorescent probes using biomass waste as a precursor may have much higher potential. Here we transformed the biomass waste of peach leaves into value-added fluorescent CQDs through a low-cost and green one-step hydrothermal process. The obtained CQDs show excitation-dependent photoluminescence properties with a fluorescence lifetime of 5.96 ns and a quantum yield of 7.71% without any passivation. In addition, the CQDs have a fine size of 1.9 nm with good hydrophilicity and high fluorescent stability over pH 4.0–11.0 range. Fluorescence imaging of in vitro cell cultures and in vivo with zebrafish show that CQDs possess ultra-low toxicity and remarkable performance for biological imaging. Even when CQDs present at a concentration as high as 500 µg/mL, the organism can still maintain more than 90% activity both in vitro and in vivo, and present bright fluorescence. The cheaper, greener, ultra-low toxicity CQDs developed in this work is a potential candidate for biological imaging in vitro and in vivo. Green extraction of value-added carbon quantum dots from peach leaves waste with ultra-low toxicity and excellent photoluminescence properties: A potential candidate for biological imaging in vitro and in vivo. [Display omitted]